Drde-07: a possible antidote for sulphur mustard toxicity - Gautam, A.; Vijayaraghavan, R. (Cellular and Molecular Biology, 2010)
Chemical Warfare Agents are classified in various categories and vesicating agents are one among them. Vesicating agents are mostly mustard agents. Sulphur mustard which is chemically known as bis(2-chloro ethyl) sulphide (SM), was first used in World War-I and in recent past in Iran-Iraq war. Its possible use by the terrorist groups can’t be overlooked in the present scenario. As the mode of its action is still lacking, no specific treatment is so far known against SM induced systemic toxicity. The major drawback with the development of antidote against sulphur mustard is low efficacy of the potential compounds in vivo models. This review summarizes the current update about the work done so far and the future stratagies.